Toxic Academic Culture in East Asia - Yang, Rui (International Higher Education, 2016)
East Asian societies’ recent progress in higher education has been severely tarnished by a toxic academic culture. With the exception of Japan where academic culture has been substantially better developed, an academic culture that is based on meritocratic values, free inquiry, and competition is largely absent in East Asian societies. The rotten academic culture has casted a blight over East Asia’s ambitious aspiration to world-class universities, despite the region’s recent strides on the research stage and huge investment in higher education.